Management of Clinical Supervision of Principals in Improving the Performance of Islamic Religious Education Teachers in SD Negeri 13 Tuapejat Kecamatan Sipora Utara Kabupaten Kepulauan Mentawai - Mugianto, Mugianto (Program Pascasarjana UMSB, 2024)
This article discusses about the management of clinical supervision of principals in improving Islamic Religious Education teachers’ performance in Tuapejat Public Primary School 13 North Sipora District of Mentawai Islands Regency. The study employed descriptive qualitative research methods, instruments and data collection procedures i.e. data collection methods in research i.e. interviews, observation and documentation. The three activities in data analysis are data reduction, data presentation, and inference drawing/verification. To check the credibility of the data using the following techniques: Persistent observation, triangulation, member check, and referential adequacy check. Results of the study: 1) The planning of clinical supervision of the principal in improving the performance of Islamic Religious Education teachers in SD Negeri 13 Tuapejat is conducted by the principal per semester, supervision is implemented twice a year, with planning a) understanding teachers and preparation, b)supervising supplies pre-observation schedule, c) holding an initial discussion to determine the observation schedule, d) reminding the teacher of anything that needs to be prepared; 2) Implementation of principal’s clinical supervision in improving Islamic Religious Education teachers’ performance of 13th Tuapejat State Primary School namely: a) Drafting clinical supervision objectives, b) Preparing observation instruments, c) Setting observation plans, d) Implementing observations , e) Giving feedback f) Formulating a follow-up plan; 3) Opportunities and challenges of principals’ clinical supervision in improving PAI teachers’ performance of Tuapejat State SD 13 namely a) paying attention to teaching ability, b) preparing the resources needed by PAI teachers, c) building cooperative relationships between principals and teachers, d ) setting goals the obvious for teachers, e) designing effective follow-ups to help improve teacher performance; f) Clinical supervision evaluation.Keyword : Clinical Supervision Management, Principals, Islamic Religious Education Teacher Performance